THE MOST COMMON DERMATOLOGICAL CONDITIONS IN INFANTS IN PRIMARY CARE SETTINGS – A REVIEW - Marta Janura; Maja Weimann; Hanna Barska-Kobylińska; Martyna Byrska; Grzegorz Przywara; Oliwia Biegańska; Emilia Biczak; Ewa Katarzyna Malaka; Marlena Zubiak; Sara Langner (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Dermatological conditions are among the most common health issues affecting infants. These include atopic dermatitis, seborrheic dermatitis, and diaper dermatitis. Most cases can be successfully treated by primary care physicians. However, if left untreated, they can lead to chronic skin problems, inflammation, superinfection, and systemic symptoms.Study objective: The aim of this study is to analyze the prevalence of dermatological conditions within the infant population, identify the most frequently occurring disorders and evaluate current treatment approaches available in primary care settings, based on up-to-date medical evidence.Materials and methods: A literature review was conducted using PubMed to collect all available and current medical knowledge regarding the most common dermatological conditions in infants.Conclusions: Studies have shown that in dermatological diseases in infants proper skincare plays a major role as a preventative and as a treatment. Nevertheless, in some cases there is a need to use prescription remedies. Better education in newborns’ parents can reduce occurrence of dermatological diseases such as atopic dermatitis, seborrheic dermatits and diaper dermatitis.